Out-of-Pocket Health Expenditures and Health Care Services Use Among Older Americans With Cognitive Impairment: Results From the 2008-2016 Health and Retirement Study - Jenkins, Derek; Stickel, Ariana; González, Hector M; Tarraf, Wassim (The Gerontologist, 2022)
The evidence base on health services use and cost burdens associated with transition to severe cognitive impairment (SCI) and dementia is underdeveloped. We examine how the change in cognitive impairment status influences nursing home use, hospitalizations, and out-of-pocket (OOP) expenditures. We use prospective data from the Health and Retirement Study (2007/2008-2015/2016) on adults 70 years and older meeting research criteria for cognitive impairment not dementia (CIND) at baseline (unweighted n = 1,692) to fit 2-part models testing how reversion to normal cognition, stability (CIND maintenance), and transition into SCI/dementia influence change in yearly nursing home use, hospitalizations, and OOP expenditures. Over 8 years, 5.9% reverted, 15.9% remained CIND, 14.9% transitioned to SCI/dementia, and 63.3% died. We observed substantial increases in the propensity of any nursing home use which were particularly pronounced among those who transitioned or died during follow-up and similar but less pronounced differences in patterns of inpatient hospitalizations. Average baseline OOP spending was similar among reverters ($1156 [95% confidence interval = 832-1,479]), maintainers ($1,145 [993-1,296]), and transitioners ($1,385 [1,041-1,730]). Individuals who died during follow-up spent $2,529 (2,101-2,957). By the eighth year of follow-up, spending among reverters increased to $1,402 (869-1,934) and $2,188 (1,402-2,974) and $8,988 (5,820-12,157) for maintainers and transitioners, respectively. Average spending at the wave preceding death was $7,719 (4,345-11,094). Estimates were only partly attenuated through adjustment to covariables. A better understanding of variations in health services use and cost burdens among individuals with mild cognitive impairment can help guide targeted care and financial planning.